The Worlds of Petrarch - Mazzotta, Giuseppe, 1942- (Book collections on Project MUSE., 1993)
At the center of Petrarch's vision, announcing a new way of seeing the world, was the individual, a sense of the self that would one day become the center of modernity as well. This self, however, seemed to be fragmented in Petrarch's work, divided among the worlds of philosophy, faith, and love of the classics, politics, art, and religion, of Italy, France, Greece, and Rome. In recent decades scholars have explored each of these worlds in depth. In this work, Giuseppe Mazzotta shows for the first time how all these fragmentary explorations relate to each other, how these separate worlds are p.